A small-molecule FRET reporter for the real-time visualization of cell-surface proteolytic enzyme functions - Mu, Jing (2015)
Real-time imaging of cell-surface-associated proteolytic enzymes is critical to better understand their performances in both physiological and pathological processes. However, most current approaches are limited by their complexity and poor membrane-anchoring properties. Herein, we have designed and synthesized a unique small-molecule fluorescent probe, which combines the principles of passive exogenous membrane insertion and Förster resonance energy transfer (FRET) to image cell-surface-localized furin-like convertase activities. The membrane-associated furin-like enzymatic cleavage of the peptide probe leads to an increased fluorescence intensity which was mainly localized on the plasma membrane of the furin-expressed cells. This small-molecule fluorescent probe may serve as a unique and reliable reporter for real-time visualization of endogenous cell-surfaceassociated proteolytic furin-like enzyme functions in live cells and tissues using one-photon and two-photon microscopy.